KEPASTIAN HUKUM TERHADAP GUGATAN WANPRESTASI DALAM PERJANJIAN LISAN - Priscilia; Syaputri, Martika Dini (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
An oral agreement is an employment relationship that exists without an employment contract. In social life, verbal agreements are often made. However, in social life, verbal agreements are often made without the person realizing it and have shortcomings when presentes as evidence in court. The purpose of this writing is to determine the legal certainty of oral agreements and how to resolve claims for breach of contract in oral agreements. The research method used is normative legal research. The types of data used are secondary data and primary data which are based on literature, books and various legal regulations and previous research. All data was analyzed using qualitative analysis. The results of this research show that verbal agreements are valid for everyone based on clause 1338 of the Civil Code which explains that all agreements made legally are considered valid by the person who makes them. However, to prove this, witnesses or confessions from the parties involved are needed, then this dispute can be resolved by undergoing a mediation process based on the agreement of the parties and the advantage of this mediation is that the parties do not need to defend the facts and evidence that are in front of them.